Revisiting thiol‐yne chemistry: Selective and efficient monoaddition for block and graft copolymer formation. Issue 2 (18th August 2014) - Sprafke, Johannes K.; Spruell, Jason M.; Mattson, Kaila M.; Montarnal, Damien; McGrath, Alaina J.; Pötzsch, Robert; Miyajima, Daigo; Hu, Jerry; Latimer, Allegra A.; Voit, Brigitte I.; Aida, Takuzo; Hawker, Craig J.
ABSTRACT The untapped potential of radical thiol‐yne mono‐addition chemistry is exploited to overcome the known limitations of thiol‐ene chemistry in polymer coupling and block copolymer formation. By careful choice of alkyne, the reaction can selectively lead to the mono‐addition product with efficiencies surpassing those achieved by traditional thiol‐ene chemistry. This improvement is illustrated by the nearly quantitative synthesis of a variety of diblock and graft copolymers. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 319–326